Hadith berkaitan penyakit al-'Ayn: Analisis hubungannya dengan pukau dan pemahaman dalam kalangan masyarakat Malaysia / Mohamad Khairul Faiz Mohd Khadzali - Mohamad Khairul Faiz , Mohd Khadzali (2021)
Evil Eye is a type of act that is associated with pukau. There was no prominent debate among the Malaysian community about the evil eye, but discussions and cases of poaching took place through reports from news, newspapers and social media. Furthermore, the explanation of the evil eye among Islamic medical practitioners is also unclear, and some are even confused about the actual understanding by associating it with pukau. This study aims to explain from the point of view of the true understanding of the evil eye from the fiqh al-hadith angel and explains its relationship with pukau as well as analyses the understanding of Malaysian society between the two. Through quantitative analysis, a total of 458 respondents were involved in answering the questionnaire as a research instrument. The questionnaire contained 36 items using Likert scale measurements. The reliability value of the study instrument is 0.87. The data were analysed by using Statistical Package for the Social Science (SPSS) version 22.0. The results of the study found that the evil eye and pukau are two different things in which the evil eye is something that affects the soul of its victim so as to bring harm to its victim due to jealousy and amazement. While pukau is a magic practice that uses the help of jinn to influence the human mind through touch, sight, smoke and so on. From the analysis of hadith from al-Kutub al-Sittah, there are 43 hadiths that discuss the evil eye, which can be divided into 11 themes, and it can be concluded that the fact of the evil eye is real and there are certain treatment methods of the Prophet SAW in treating the disease of al- 'Ayn. However, as a whole, there is no direct relationship of evil eye with pukau except in few aspects. Among the aspects are, firstly, both can be in effect without the use of the eye. Secondly, both affect human souls and as a result harms the victim. Thirdly, one of the reasons that the victim might be chosen or random is due to displaying the prosperities possessed through the social media as well as to the public. From the field study, it was found that the understanding of the community is at a moderate level because out of 36 items from questionnaire posed only 20 the majority answered correctly. Thus, in the view of the researchers, the community still do not fully understand about the evil eye, which may be unusual in society, but they know and understand about pukau.